Exploring Individual Mental Health Issues: A Qualitative Study among Fellowship-Trained Sports Medicine Physicians - Stavitz, James; Eckart, Adam; Ghimire, Pragya (International journal of environmental research and public health, 2023)
The mental health of fellowship-trained sports medicine physicians (FTSMPs) around the United States is a subject that needs additional exploration. Currently, there is little research exploring how FTSMPs address their mental health on a routine basis. Using the theory of secondary trauma stress to help navigate this study, the purpose of this expressive, all-purpose qualitative study is to improve the understanding of FTSMPs’ perceptions of their mental health and the kinds of strategies used to manage these issues. This is a general qualitative study. All interviews were conducted via video communication platforms such as Zoom. The final sample included 35 FTSMPs: 25 men and 10 women. Data collection used a semi-structured interview approach. Data analysis was carried out using NVivo 12 qualitative data analysis software. Four themes emerged: mental health matters affect individual daily lives of FTSMPs; FTSMPs correlate mental health struggles with stress and anxiety; FTSMPs experience barricades when seeking support for mental health issues; and FTSMPs have poor mental health support-seeking behaviors. Results highlight openings for hospitals and private practice institutions, including producing a maintainable work–life equilibrium for FTSMPs and offering these FTSMPs access to mental health services. These recommendations may diminish exhaustion amongst several FTSMPs, a product detrimental to patients, providers, and hospitals.